OPTIMALISASI PEMBELAJARAN MAHASISWA ADMINISTRASI PENDIDIKAN MELALUI KEGIATAN KULIAH TAMU BERBASIS EXPERIENCE SHARING - Trisnawati, Septian Nur Ika; Muflihin, Muh Hizbul (Tahta Media Grup, 2025)
This service aims to describe the effectiveness of guest lectures based on experience sharing in bridging the gap between theory and practice in the Education Administration course in the Islamic Education Study Program (PAI). The method used is descriptive-qualitative with a participatory approach cici4d. The activity was carried out online by presenting the Professor of Educational Administration as the main speaker and involving 158 fifth-semester students. The learning process included presentations, case studies, interactive discussions, and reflections. The results showed that this guest lecture activity succeeded in creating an interactive, dialogical, and reflective learning atmosphere. Students gained a more concrete understanding of the implementation of Islamic education administration in the field, as well as fostering critical thinking skills and awareness of cici4d spiritual values such as honesty and blessings in educational leadership. In addition, this activity strengthens the synergy between the academic and professional worlds and opens up opportunities for strategic collaboration. In conclusion, guest lectures based on experience sharing proved to be an effective learning strategy in improving the academic and practical competencies of PAI students. This model can be used as a strategic innovation to be applied to other courses that require managerial and contextual understanding based on Islamic values.